Ionizing Radiation-Induced Immune and Inflammatory Reactions in the Brain - Lumniczky, Katalin; Szatmári, Tünde; Sáfrány, Géza (Frontiers in Immunology, 2017)
Radiation-induced late brain injury consisting of vascular abnormalities, demyelination, white matter necrosis and cognitive impairment has been described in patients subjected to cranial radiotherapy for brain tumours. Accumulating evidence suggests that various degrees of cognitive deficit can develop after much lower doses of ionizing radiation, as well. The pathophysiological mechanisms underlying these alterations are not elucidated so far. A permanent deficit in neurogenesis, chronic microvascular alterations and blood-brain barrier dysfunctionality are considered among the main causative factors. Chronic neuroinflammation and altered immune reactions in the brain, which are inherent complications of brain irradiation, have also been directly implicated in the development of cognitive decline after radiation. The present review aims to give a comprehensive overview on radiation-induced immune alterations and inflammatory reactions in the brain and summarizes how these processes can influence cognitive performance. The available data on the risk of low dose radiation exposure in the development of cognitive impairment and the underlying mechanisms are also discussed.